Unraveling the role of the enigmatic MatK maturase in chloroplast group IIA intron excision - Barthet, Michelle M. (Plant Direct, 2020)
Maturases are prokaryotic enzymes that aid self‐excision of introns in precursor RNAs and have evolutionary ties to the nuclear spliceosome. Both the mitochondria and chloroplast, due to their prokaryotic origin, encode a single intron maturase, MatR for the mitochondria and MatK for the chloroplast. MatK is proposed to aid excision of seven different chloroplast group IIA introns that reside within precursor RNAs for essential elements of chloroplast function. We have developed an in vitro activity assay to test chloroplast group IIA intron excision. Using this assay, we demonstrate self‐excision of the group IIA intron of the second intron of rps12 and the group IIA intron of rpl2. We further show that the addition of heterologously expressed MatK protein increases efficiency of group IIA intron self‐splicing for the second intron of rps12 but not the group IIA intron of rpl2. These data, to our knowledge, provide the first direct evidence of MatK’s maturase activity.